Application of the MADM Method for the Admission System for Islamic Religious Trustees - Sawitha Yuliana Rinaldy; Aridhanyati Arifin (Universitas Negeri Medan, 2022)
The selection process for Islamic tutor and the decision to pass or fail is made by subjective views of the selector. The konvensional process takes a lot of time. It is necessary to have Decision Support System (DSS) to minimize the subjective side of the selectors and streamline the selection process so that effective decision can be obtained. The character of this problem matches the characteristic of Multi Attribute Decision Making (MADM) model. A combination of Simple Addictive Weighting (SAW) and Technique for Others Reference by Similarity to Ideal Solution (TOPSIS) are selected to solve MADM model. SAW used to rank decision while TOPSIS used to calculate level 2 criteria. Based on testing of 30 data samples using Single Detection Threshold method, the system performance accuracy rate is 83,33% and precision rate is 77%. The combination of the two method has been successfully applied and provide accurate and precise recommendations.